2011
DOI: 10.1016/j.jamcollsurg.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Play a Critical Role in the Systemic Inflammatory Response and End-Organ Injury Resulting from Trauma

Abstract: Background Much of the morbidity following trauma results from excessive activation of the innate immune system. This is manifested as a systemic inflammatory response and associated end-organ damage. Although mast cells are known to be important in many immune responses, their role in the systemic response to severe trauma is unknown. Study Design C57BL/6J-KitW-sh/BsmJ (mast cell deficient) and wild type mice were subjected to 1.5h of hemorrhagic shock plus bilateral femur fracture and soft tissue injury (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…Consistent with our previous reports (20), we found that both lung injury (Figure 2, A–L) and liver injury (Figure 2, M–X) were maximal between 6 and 24h. Lung injury was assessed by histology and lung injury score (Figure 3, A–C) while liver damage was assessed histologically and by circulating levels of ALT (Figure 3, D–F).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our previous reports (20), we found that both lung injury (Figure 2, A–L) and liver injury (Figure 2, M–X) were maximal between 6 and 24h. Lung injury was assessed by histology and lung injury score (Figure 3, A–C) while liver damage was assessed histologically and by circulating levels of ALT (Figure 3, D–F).…”
Section: Resultssupporting
confidence: 93%
“…were given as necessary throughout the course of the experiment. Bilateral Pseudofracture (PF) and hemorrhagic shock (HS) were performed as previously described by our group (19, 20). Briefly, donor mice were euthanized via overdose of pentobarbital and the femurs and tibias were removed from both hind limbs and crushed using a sterile mortar and pestle in the biohazard hood.…”
Section: Methodsmentioning
confidence: 99%
“…Similar macrophage-induced increases in fibrous tissue formation leading to defective healing of skin wounds have been associated with LPS-induced systemic inflammation [37]. In addition to macrophages, mast cells have been implicated in the immune response to trauma in a mouse model of acute systemic inflammation [9]. The systemic inflammatory response and end organ (liver, lung) damage 6 hours after being subjected to hemorrhagic shock and femoral fracture were less severe in mast cell-deficient KitW-sh mice compared with wild type mice.…”
Section: Discussionmentioning
confidence: 90%
“…The systemic inflammatory response and end organ (liver, lung) damage 6 hours after being subjected to hemorrhagic shock and femoral fracture were less severe in mast cell-deficient KitW-sh mice compared with wild type mice. Cai et al [9] concluded from their data that mast cells play a key role in the systemic inflammatory response. In previous work we characterized healing of the femoral bone defect used in the current study in mast cell-deficient KitW-sh mice [6].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence is distant organ injury, predominantly affecting the lungs (3)(4)(5). Limb trauma followed by injury to distant organs is likely responsible for the high morbidity and mortality observed (6)(7)(8). Therefore, therapeutic interventions to treat or block these "cascade" consequences are needed to improve outcomes of such patients (9,10).…”
mentioning
confidence: 99%